Praktikum Sederhana Pembelajaran IPA untuk Meningkatkan Hasil Belajar Kognitif dan Keterampilan Proses Sains di MI Al Hikmah Kajen Pati - Nikmah, Farikhatun; Zahrinna, Alfi; Jalil, Muhamad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Science learning needs to be packaged in an attractive way so that students are enthusiastic about learning. This study aims to determine the increase in science skills with simple practical methods in class VI MI Al Hikmah Kajen Pati students. This study aims to determine the increase in cognitive learning outcomes and science process skills with simple practical methods in class VI students of MI Al Hikmah Kajen Pati. This study uses quantitative research. Data collection was carried out by conducting a pretest and posttest to students and observations by the observer. Data analysis techniques in this study used descriptive analysis and hypothesis testing. The results showed that the significance value of the WilcoxonTest Table was 0.000 so <0.05, meaning that Hawas accepted. So there is a difference between the learning outcomes of class VI MI Al-Hikmah Kajen Pati students after using a simple practicum.The results of experimental or research findings on science process skills can be seen from the indicators of identification of tools and materials as well as data on the results of experiments students complete with a percentage of 80%, on the indicator of answering and asking questions students complete with a percentage of 62.5%, on the indicator of conveying the results of discussions in a clear, precise and effective students complete with a percentage of 90%, on the indicator of choosing the appropriate theory (reference) students complete with a percentage of 85%.